2001
DOI: 10.2165/00129785-200101010-00008
|View full text |Cite
|
Sign up to set email alerts
|

DNA: Still A Target Worth Aiming At?

Abstract: DNA acts as the final target for most clinically effective cytotoxic agents, but the lack of selectivity for tumor cells has raised questions about the value of developing new DNA-interactive agents. Three new classes of cytotoxic agents are reviewed; each interacts directly with DNA but cytotoxicity appears to be mediated through novel mechanisms, including the interaction with specific proteins by DNA-bound drug molecules. Irofulven is the lead compound of the illudin family of molecules. It causes a novel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the presence of PTGR1 and NADPH or rat liver cytosol, AF has been shown to preferentially alkylate purine bases as single nucleosides and in ctDNA, and the corresponding adducts have been detected in cells. The major DNA adducts, 3-AF-deoxyadenosine (3-AF-dAdo) and 7-AF-deoxyguanosine (7-AF-dGuo), formed by AF in the presence of PTGR1 and NADPH, are thermally unstable and depurinate during neutral thermal hydrolysis 29 (Scheme 4). These adducts have been previously identified and characterized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of PTGR1 and NADPH or rat liver cytosol, AF has been shown to preferentially alkylate purine bases as single nucleosides and in ctDNA, and the corresponding adducts have been detected in cells. The major DNA adducts, 3-AF-deoxyadenosine (3-AF-dAdo) and 7-AF-deoxyguanosine (7-AF-dGuo), formed by AF in the presence of PTGR1 and NADPH, are thermally unstable and depurinate during neutral thermal hydrolysis 29 (Scheme 4). These adducts have been previously identified and characterized.…”
Section: Resultsmentioning
confidence: 99%
“…5 was reacted with dAdo, dGuo, or ctDNA in aqueous solution (pH 7) at 37 °C for 24 hours. Samples were heated to 90 °C to induce hydrolysis 29 of modified bases. After removal of water by rotary evaporation, the dried mixture was reconstituted in methanol and assayed by LC-MS to determine whether 3-AF-Ade and 7-AF-Gua were formed.…”
Section: Resultsmentioning
confidence: 99%
“…Ecteinascidin 743 (ET-743) inhibits DNA synthesis (therefore cell proliferation) and is in clinical trials for cancer [138,139]. Phase II clinical trials have demonstrated efficacy with ET-743 as a first or second-line treatment of advanced soft-tissue sarcoma [140,141]. ET-743 is an example of potential chemotherapeutic agents targeting DNA synthesis discovered through serendipitous screening.…”
Section: Macromolecule Synthesismentioning
confidence: 99%